Oral competency test: difficulties in the MUET preparatory course in tertiary setting / Caesar DeAlwis - DeAlwis, Caesar (2011)
Fluency in English is a major yardstick by which the marketability of a graduate is assessed. In gearing graduates towards world class standards, competency in the English language has always been stressed upon. As such, the English Language has been an essential component of the academic curriculum in tertiary institutions. Among the many courses offered are the basic language and proficiency courses. The aim of this paper is to examine the difficulties faced by undergraduates and examiners while undertaking the MUET Speaking Test in tertiary setting. The results show it would help if the papers set were of the level of the students' ability. The paper also provides suggestions and guidelines about how the Speaking test in tertiary setting may be improved.